Epistemic diversity as methodological incommensurability (2023)
ABSTRACT: The thesis of epistemic diversity holds that there are different epistemic systems. An epistemic system is a complex set of conditions that a group of knowers adopts for the production, evaluation and legitimization of knowledge. These include epistemic norms, social imaginaries, and cognitive habits (Dotson, 2014). At first sight, "epistemic system" seems to coincide with "paradigm". However, the notion of paradigm, as Kuhn characterized it in The Structure of Scientific Revolutions (1970), entails ontological and epistemological commitments that result in the possibility of semantic incommensurability. According to Kuhn, two rival theories are incommensurable when it is impossible to find a common language that allows inter-theoretical translation between the theories in dispute. This type of incommensurability is manifests in translation failures and communication problems between rival theories. The talk will argue that the notion of epistemic system relevant to the characterization of epistemic diversity does not imply such commitments. However, it does imply that there is methodological incommensurability between different theories. This incommensurability holds between different epistemic systems in relation to epistemic values, criteria of legitimacy, relevance, and evaluation of theories. Traditionally, three possible scenarios have been analyzed (Rosa-Pérez, 2000): 1. Methodological incommensurability occurs when two epistemic systems share the same concepts at the level of epistemic values (e.g., precision, simplicity, elegance, predictive fecundity, explanatory fecundity, empirical adequacy), but assign different weights to these values in the evaluation of theories. 2. Methodological incommensurability occurs when there is agreement on the weight assigned to epistemic values, but there is no agreement on the application of that value to specific explanations (?). 3. Methodological incommensurability occurs when epistemic systems differ in the list of legitimate problems and solutions according to epistemic values. The talk argues that there are two additional scenarios that the prior classification fails to account for: 4. There is methodological incommensurability when an epistemic system declares the insufficiency of the epistemic values accepted by a rival epistemic system. 5. There is methodological incommensurability when an epistemic system declares the inadequacy of the epistemic values accepted by a rival epistemic system. These two types of methodological incommensurability are analyzed for the purpose of extending the characterization of epistemic diversity.